SUBSTITUSI TEPUNG KEPALA IKAN LELE DUMBO (Clarias Gariepinus sp) UNTUK MENINGKATKAN KANDUNGAN KALSIUM CRACKERS - Herviana Ferazuma; Sri Anna Marliyati; Leily Amalia (Food and Nutrition Society of Indonesia, 2011)
The using of fish by-products has not been optimally developed in food processing. The objective of this research was to study the using of catfish's head flour as a part of material in formulating crackers to increase its calsium content. The method for making this flour was based on thermal process using drum dryer. The physical and chemical properties were analysed. Crackers was formulated by using catfish's head flour with trial and error method. The formulations were then F0 (0:100), F1 (7,5:92,5), F2 (12,5:87,5), F3 (17,5:82,5), and F4 (22,5:77,5). F1 and F2 crackers were chosen formulations based on organoleptic test. The result of chemical analysis were respectively: moisture 2,4-3,3% (wb), ash 3,7-4,97% (wb), protein 9,9-11,4% (wb), lipid 19,2-20,5% (wb), carbohydrate 63,9-69,6% (wb), and energy 480-484 kkal (wb). F1 crackers contained 0,3634% of calcium (wb) while F2 crackers contained 0,3147% of calcium (wb). The phospor's content in F1 and F2 crackers were respectively: 0,2362% (wb) and 0,3147% (wb). The contribution of calcium content in crackers were calculated based on RDA (Recommended Dietary Allowance) for children, adolescents, and adults. F1 crackers fulfilled calcium’s RDA respectively : 25,8% for children; 15,5% for adolescents, and 19,3% for adults. F2 crackers fulfilled calcium’s RDA respectively: 39,9% for children; 23,9% for adolescents, and 29,9% for adults. The amount of crackers that should be consumed was at least as much 44 gram/day. Key words: catfish's head flour, crackers, calcium content